Islamic educational mobile application based on play therapy for autism children / Sarah Nisa Ali …[et al.] - Ali, Sarah Nisa; Mohd Zin, Nor Asma; Abdul Rahman, Noorihan; Ahmad, Marina; Arifin, Noorfadzilah; Manaf, Maznie; Yusof, Rozianiwati (Universiti Teknologi MARA, Kelantan, 2023)
Autism Spectrum Disorder (ASD) is becoming more prevalent among children worldwide. Three main issues that affect ASD children are behavior, communication, and social interaction. Children with special needs have the same right to engage in education, especially religious education. The main concern in delivering education to these special children is how to maximize their learning. They need teachers and parents to recognize their unique needs and abilities. ASD children have problems staying focused in learning. They are also not interested in lengthy content and linear materials such as books. Currently, the development of mobile applications is growing as many could benefit from it. This research will suggest a development of an Islamic educational mobile application for ASD children, which is built on the idea of enhancing visual and attentional skills based on play therapy. Since it is commonly known that children with ASD do not play in the same manner as regular children, the use of play therapy with ASD children has gained attention as a research topic. Auto play therapy is the term for the play therapy used with children who have ASD. The Mobile Application will include parent's engagement as well for learning monitoring. This project was developed using Mobile Application Development Life Cycle (MADLC). The result and findings defined that most users agreed that this mobile application was easy to use, not complex, consistent, integrated well with elements and they are willing to use it frequently.